Islamic Education And Democracy: Harmonizing Faith And Civic Engagement - Ahmad Reza Maulana; Arga Sabda Wiguna; Muhammad Fajriansyah Solichin; Muhammad Reza Syahbudi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This study explores the intersection of Islamic education and democratic principles, focusing on their historical context and core tenets. Historically, Islamic education has emphasized knowledge, ethics, and community welfare, aligning with many democratic ideals such as equality and civic engagement. This research examines the compatibility between Islamic values and democratic principles, arguing that both systems advocate for justice, participation, and the common good. However, integrating these frameworks presents challenges, including criticisms regarding potential conflicts between religious doctrines and democratic freedoms. Despite these challenges, the benefits of harmonizing Islamic education with democracy are significant. Such integration can foster a more inclusive, ethically grounded civic society, enhancing mutual respect and cooperation. This study aims to contribute to the ongoing discourse on how educational practices rooted in Islamic teachings can enrich democratic processes, ultimately promoting a balanced approach to faith and civic responsibility.